Identificación del bento presente en camaronera ubicada en el sitio pagua cantón El Guabo - Velásquez Riofrío, Byron Antonio (2013)
Overriding consideration is that primary productivity in aquatic crops in enclosures is critical to the success of aquaculture activities, identifying the quality of water, depending on their nature. From this starting point shrimp industry in our country has been successfully developed based on research and experience acquired over time, constituting a development generating activity, economically viable, ecologically sustainable. Hence the need to understand the important role of natural food in the diet of species growing under controlled conditions. The additional power is important because it represents if the item of greatest value in operating costs of the activity, and being able to get to be in one of the main sources of pollution captive culture system and surrounding aquatic ecosystems. In order to point out this work, we proposed the following objective: 1. Qualitatively and quantitatively analyze benthic organisms found in the gut of shrimp production in ponds. The research was aimed at comparing the existing benthic community at the bottom of the ponds and in the intestinal contents of Litopenaeusvannamei. The study was conducted in the shrimp farm located in the area belonging to the canton PaguaGuabo province of El Oro and Planctonología laboratories and Aquaculture, Faculty of Agricultural Sciences of the Technical University of Machala. This work lasted four months, beginning in June of 2012 and culminated in October the same year. For statistical analysis, samples were taken weekly weights in grams and length in centimeters of shrimp found in ponds 1 pond 2 and pond 3; indicating that variations are equal and the null hypothesis is accepted. The two means are not significantly different.